Effects of drying on the production of polyphenol-rich cocoa beans. Issue 15 (18th November 2017) - Santhanam Menon, A.; Hii, C. L.; Law, C. L.; Shariff, S.; Djaeni, M.
ABSTRACT: The current study emphasizes on the effects of four drying methods, namely, oven drying, adsorption drying, freeze-drying, and vacuum drying on the total polyphenol content and antioxidant activity of unfermented cocoa beans. The comparison of drying kinetics analysis showed that adsorption drying method dried faster than other methods. On comparing the results of total polyphenol contents and antioxidant activity, freeze-drying method showed the optimal results and the lowest values were recorded by oven drying. The sensory analysis of cocoa beans after drying showed low cocoa flavor and high astringency scores.